2022
DOI: 10.1371/journal.pone.0276845
|View full text |Cite
|
Sign up to set email alerts
|

The social learning and development of intra- and inter-ethnic sharing norms in the Congo Basin: A registered report protocol

Abstract: Compared to other species, the extent of human cooperation is unparalleled. Such cooperation is coordinated between community members via social norms. Developmental research has demonstrated that very young children are sensitive to social norms, and that social norms are internalized by middle childhood. Most research on social norm acquisition has focused on norms that modulated intra-group cooperation. Yet around the world, multi-ethnic communities also cooperate, and this cooperation is often shaped by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Lewis, 2002;Takeuchi, 2014). Our work among the BaYaka and Bantu-speaking peoples in the Motaba River region of the Republic of the Congo, where the current study was conducted, has also shown that inter-group cooperation is further stabilised by shared norms of exchange, despite otherwise contrasting cultural norms regarding cooperation and resource sharing, and individual differences in goals and obligations (Jang & Boyette, 2021;Kandza et al, 2023;Pope-Caldwell et al, 2022).…”
Section: Intergroup Cooperation In Shotgun Huntingmentioning
confidence: 75%
“…Lewis, 2002;Takeuchi, 2014). Our work among the BaYaka and Bantu-speaking peoples in the Motaba River region of the Republic of the Congo, where the current study was conducted, has also shown that inter-group cooperation is further stabilised by shared norms of exchange, despite otherwise contrasting cultural norms regarding cooperation and resource sharing, and individual differences in goals and obligations (Jang & Boyette, 2021;Kandza et al, 2023;Pope-Caldwell et al, 2022).…”
Section: Intergroup Cooperation In Shotgun Huntingmentioning
confidence: 75%
“…In our future work, we hope to track a range of dynamic variables which may further help or hinder intergroup cooperation. First, we need to better understand how the cultural institutions that regulate intergroup cooperation are transmitted from one generation to the next (Bombjaková, 2018;Bunce & McElreath, 2017;Pope-Caldwell, Lew-Levy, et al, 2022). Specifically, it would be interesting to investigate whether success biases play a role in the spread of hiding kills or cartridges and other behaviors which lead to higher payoffs for BaYaka (McElreath et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Group identification may be based on physical features such as proximity, residence, or relatedness, or social structures such as band or clan membership, indicated through dress or decoration. The capacity to identify ourselves and others as members of social groups that share certain properties allows us to interact with strangers not just as strangers; instead, we can base our treatment of them on their group membership and expect them to do the same in return (Lew- Levy, Lavi, Reckin, Cristóbal-Azkarate, & Ellis-Davies, 2018;McElreath, Boyd, & Richerson, 2003;Pope-Caldwell et al, 2022). Once norms governing relationships with out-groups are in place for both interacting groups, individuals can be reasonably confident about how they will be treated by members of the other group and able to calculate whether the interaction will be positive.…”
Section: Norms Reduce Uncertainty In Intergroup Relationshipsmentioning
confidence: 99%